2022
DOI: 10.1155/2022/1192902
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Dynamic Changes of Microcirculation Flow, Tissue Perfusion Parameters, and Lactate Level and Mortality of Septic Shock in ICU

Abstract: Background. Septic shock is a common clinical critical disease with high mortality, hemodynamic instability, and easy to be complicated with multiple organ failure. The rapid progress of the patient’s condition poses a serious threat to patient’s safety. Aim. To investigate the relationship between the dynamic monitoring of microcirculation perfusion parameters and blood lactic acid level and the prognosis of patients with infection shock in ICU. Methods. A total of 104 patients with septic shock admitted to I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Recent study has demonstrated a correlation between lactate levels and adverse outcomes in critically ill patients ( 25 ). Furthermore, research has indicated an association between elevated lactate levels and a poor prognosis in sepsis patients ( 26 ). Our study also observed elevated serum lactate levels in SMI patients with a poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Recent study has demonstrated a correlation between lactate levels and adverse outcomes in critically ill patients ( 25 ). Furthermore, research has indicated an association between elevated lactate levels and a poor prognosis in sepsis patients ( 26 ). Our study also observed elevated serum lactate levels in SMI patients with a poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in 35 patients with septic shock, P cv-a CO 2 /C a-cv O 2 was a strong predictor of lactate behavior, and both variables were associated with mortality [90]. Recent studies also found a relationship of P cv-a CO 2 /C a-cv O 2 to mortality [91][92][93].…”
Section: The Clinical Usefulnessmentioning
confidence: 92%
“…However, some studies (43) have indicated that the combination of TP and NE does not improve microcirculation, suggesting that microcirculation is primarily influenced by factors such as patient volume status, resuscitation duration, and disease progression. The latest guidelines from the "Rescuing Sepsis Campaign" emphasize the importance of relying on microcirculation to guide resuscitation strategies, necessitating adjustments to existing treatment approaches and aiming for more accurate clinical predictions (44). The inconsistent results reported in the aforementioned studies can be attributed to variations in study subjects, conditions for evaluating microcirculation, and strategies used for TP infusion (45,46).…”
Section: Effect Of Tp Combined With Ne In Terms Of Fluid Resuscitationmentioning
confidence: 99%